MODERN METHODS OF EARLY DIAGNOSIS OF GLOMERULONEPHRITIS - Ergashov Bekhruzjon Komilovich (TADQIQOTLAR.UZ, 2024)
Abstract: Etiology of glomerulonephritis, development of the disease, consequences of the disease, modern methods of early diagnosis of the disease, development of treatment measures for the disease